Change-Related Acceleration Effects on Auditory Steady State Response - Sugiyama, Shunsuke; Kinukawa, Tomoaki; Takeuchi, Nobuyuki; Nishihara, Makoto; Shioiri, Toshiki; Inui, Koji (Frontiers in Systems Neuroscience, 2019)
Rapid detection of sensory changes is important for survival. We previously used change-related cortical responses to study the change detection system and found that generation of a change-related response was based on sensory memory and comparison processes. However, whether change-related cortical responses reflect processing speed remains unclear. In the present study, we simultaneously recorded auditory steady state response (ASSR) and change-related response using magnetoencephalography to study acceleration effects of sensory change events. Twelve healthy human subjects (four females and nine males) completed an oddball paradigm with a sudden sound pressure change as the test stimulus, i.e., the control stimulus was a train of 25-ms pure tones at 75 dB for 1200 ms, while the 29th sound at 700 ms of the test stimulus was replaced with a 90-dB tone. Then, we compared the latency of ASSR among four probabilities of test stimulus (0, 25, 75, and 100%). For both the control and test stimulus, stronger effects of acceleration on ASSR were observed when the stimulus was rarer. This finding indicates that ASSR and change-related cortical responses depend on physical changes as well as sensory memory and comparison processes, ASSR was modulated without peripheral inputs, and brain areas higher than the primary cortex were involved in exerting acceleration effects. Furthermore, the reduced ASSR latency clearly indicated that a new sensory event increased the speed of ongoing sensory processing. Thus, changes in ASSR latency are a sensitive index of accelerated processing.